The transformation of Torah from scribal advice to law - Fitzpatrick-McKinley, Anne (Journal for the study of the Old Testament. Supplement series, 1999)
Recent discussion of biblical law sees it either as a response to socio-economic factors or as an intellectual tradition. In either case it is viewed as the product of elites that form an international community drawing on a common culture. This book takes that fundamental discussion a step further by proposing that 'law' is an inappropriate term for the biblical codes, and that they represent, rather, the 'moral advice' of scribes working independently of the legal framework and appealing to Yahweh as authority. Only by prolonged exegesis and through the transformation of Judaean religion doe.